Unraveling lipid and inflammation interplay in cancer, aging and infection for novel theranostic approaches - Conde-Torres, Daniel; Blanco-González, Alexandre; Seco-González, Alejandro; Suárez-Lestón, Fabián; Cabezón, Alfonso; Antelo-Riveiro, Paula; Piñeiro, Ángel; García-Fandiño, Rebeca (Frontiers in Immunology, 2024)
The synergistic relationships between Cancer, Aging, and Infection, here referred to as the CAIn Triangle, are significant determinants in numerous health maladies and mortality rates. The CAIn-related pathologies exhibit close correlations with each other and share two common underlying factors: persistent inflammation and anomalous lipid concentration profiles in the membranes of affected cells. This study provides a comprehensive evaluation of the most pertinent interconnections within the CAIn Triangle, in addition to examining the relationship between chronic inflammation and specific lipidic compositions in cellular membranes. To tackle the CAIn-associated diseases, a suite of complementary strategies aimed at diagnosis, prevention, and treatment is proffered. Our holistic approach is expected to augment the understanding of the fundamental mechanisms underlying these diseases and highlight the potential of shared features to facilitate the development of novel theranostic strategies.